Caracterización socioeconómica y productiva de la parroquia rural “San Lorenzo de Tanicuchi”, del cantón Latacunga, provincia de Cotopaxi 2022. - Figueroa Uribe, Geomaira Gabriela (2022)
This research aimed the socio-economic and productive characterization of "San Lorenzo de Tanicuchi" rural parish, through the survey of territorial formation. The KoBo Toolbox software developed at Harvard University was used to carry out this activity, where a survey of 66 questions was inserted to collect indicators of social, demographic, economic, services, productive and organizational characteristics. For the number of surveys to be collected, a sample of 400 sample units for the entire parish under study was estimated using Norwegian's (1895) sample size formula or method, covering all neighborhoods and sectors of the territory. With the data obtained, it was determined that the parish of "San Lorenzo de Tanicuchi" is dominated by a female gender with 55% between 20 and 60 years of age, all of them are considered mestizos, the general level of education is secondary school with 40%. The families are made up of 3 to 4 members with 48%, and 11% of these families have a family member with a disability. In economic terms, they have 50% of their own businesses and the activity that sustains their households economically is agriculture, livestock and forestry with 41%. In terms of services, water quality is good with 82%, if they have public transportation the most used is the bus with 40%, the frequency of garbage collection is twice a week with 45%, within their unsatisfied basic needs are maintenance and road improvement, paving, sidewalks, curbs, sewage, water treatment system for human consumption and wastewater and Street lighting. Respondents perceive that 52% of the land is unsafe and 48% have been robbed or assaulted. Most of the inhabitants have irrigation systems (76%), mostly sprinkler irrigation (76%) and 22% gravity irrigation (22%), The most common crop is corn (39%) and pasture (20%). The factor that most affects the majority of their crops is pests and diseases (34%). The majority belong to the water board with 68%, and the authority that gives them the most confidence to have a good development in the parish is the perfect of Cotopaxi with 34%, and the axes of institutional support required by the University is training for crops with 19%, animal management with 13%, horticultural gardens with 12%, creation of enterprises with 10% and waste management with 8%. Due to the Covid-19 pandemic, some economic sectors were affected, which caused unemployment in the parish.